Similarities and differences in gene expression profiles of BRCA1 methylated and mutated epithelial ovarian cancers - Sahnane, Nora; Libera, Laura; Facchi, Sofia; Carnevali, Ileana; Ronchi, Susanna; Albeni, Chiara; Cromi, Antonella; Casarin, Jvan; Sessa, Fausto; Tibiletti, Maria Grazia (Frontiers in Oncology, 2023)
BRCA1 methylated (BRCA1 met ) EOC is a recently defined and not well investigated subset of neoplasms. To date, no studies have focused on the transcriptional profiles of BRCA1 met cases and, as a matter of fact, we still don't know if this subset of EOCs is similar, and to what extent, to BRCA1 mutated (BRCA1 mut ) cases. We compared a group of 17 BRCA1 met cases against 10 BRCA1 mut cases, using a subset of carefully selected 17 BRCA wt EOCs as a control group. First, BRCA1 met cases showed a downregulation of the relative transcript while this association was not observed for BRCA1 mut EOCs. BRCA1 met group exhibited a general upregulation of HR-related genes, as well as BRCA1 mut . Overall, BRCA1 met had a different gene expression profile, characterized by diffuse downregulation whereas BRCA1 mut showed a general upregulation (p<0.0001). Both BRCA1-defective groups showed a slightly activated immune response mediated by IFN gamma pathways. In conclusion, even if the expression profile of many genes related to DNA damage and repair system is shared between BRCA1 mut and BRCA1 met EOCs supporting that BRCA1 met EOCs may benefit from PARPi therapies, our data demonstrate that BRCA1 mut and BRCA1 met EOCs show different expression profiles suggesting a different mechanism of carcinogenesis that can be reflected in different responses to therapies and disease recovery.